CFD Modeling and Industrial Evaluation of a Cyclone Cascade for the Production of the HDPE Catalyst - Saeed Ovaysi (Iranian Journal of Chemical Engineering)
A new approach is proposed to evaluate various designs for gas-solid cyclone separators. This approach uses single-phase ﬂow simulation results to ﬁnd a quantitative measure of ﬂow symmetry in a given cyclone. Flow symmetry is computed by averaging imbalances of   non-axial velocities throughout the cyclone. Using this approach, two standard design methods are evaluated and the cyclone with a more symmetric ﬂow pattern is chosen as a starting point for further design improvements by reducing the diameter of its vortex ﬁnder. Two-phase computational ﬂuid dynamics (CFD) simulations compute 90.2 % collection eﬃciency for the improved design. CFD simulations reveal using a cascade of four cyclones results in an overall 99.98 % collection eﬃciency. Once installed in the actual industrial setting, the cyclone cascade achieves a 98.56 % collection eﬃciency and a particle size distribution which is in good agreement with CFD computed results.